Physical and Morphological Properties of Zirconia Produced at Different Precipitating Conditions - Andrianny Murshidi, Julie; Umor, Nurasiah; Khairul Tazril, Muhd; Yusoff M.S, Meor (Malaysian Journal of Science, 2002)
Zirconia is an important advanced material due to its structural as well as functional properties. Hydrothermal technique is one of the more common methods to produce this material and this can be achieved by precipitating zirconium hydroxide from zirconyl chloride solution. In this study, pH 8 had been selected for the precipitating condition and the zirconia was produced at different concentrations. The ratio of tetragonal to monoclinic zirconia crystalline phases was determined using X-Ray Diffraction technique. Scanning Electron Microscopy was used for analyzing the morphological structure. Other characterization techniques used include particle size analyzer for size distribution.